2020
DOI: 10.3853/j.2201-4349.72.2020.1723
|View full text |Cite
|
Sign up to set email alerts
|

Late Quaternary fossil vertebrates of the Broken River karst area, northern Queensland, Australia

Abstract: Two new fossil deposits from caves of the Broken River area, northeast Queensland, provide the first regional records of vertebrate species turnover and extinction through the late Quaternary. Fossil assemblages from Big Ho and Beehive Caves are dominated by small-bodied vertebrates, especially mammals. They represent owl roost deposits, although limited presence of larger-bodied taxa such as macropodids may be the result of occasional pitfall trapping. U-series dating demonstrates that Big Ho dates to the pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The development of ZooMS peptide markers for Australian marsupials is significant for zooarchaeological endeavours on the continent. Marsupial taxa form a significant component of Australian zooarchaeological and palaeontological assemblages, yet due to the challenges of discriminating between related taxa, they are currently rarely identified beyond the very broad family level [ 18 , 28 , 87 ]. This significantly limits the interpretive power of zooarchaeological and palaeontological studies on the continent [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of ZooMS peptide markers for Australian marsupials is significant for zooarchaeological endeavours on the continent. Marsupial taxa form a significant component of Australian zooarchaeological and palaeontological assemblages, yet due to the challenges of discriminating between related taxa, they are currently rarely identified beyond the very broad family level [ 18 , 28 , 87 ]. This significantly limits the interpretive power of zooarchaeological and palaeontological studies on the continent [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, while eastern and western grey kangaroos (M. giganteus and M. fuliginosus, respectively) share an identical set of ZooMS peptide markers, the eastern species is today found in the eastern states of Australia, while the western species occurs in the southern and western parts of Australia [84]. However, the potential for recent local extinctions as well as range shifts should not be overlooked [19,[85][86][87]. Eastern and western kangaroo ranges overlap in south-central Australia, and a recent aDNA study has demonstrated that, historically, both species were found on Kangaroo Island, whereas it was previously thought that only the western variety had roamed there [88].…”
Section: Challenges and Future Prospectsmentioning
confidence: 99%